Determinants of Innovative Work Behavior of Employees in Transjakarta Companies - Nurhalizah, Dzihniyyah Fitria; Tanuwijaya, Justine; Safitri, Zakiah Indah; Hanafi, Fitria Elvira; Nor, Norzanah Mat (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2025)
This study aims to analyze the influence of Servant Leadership, Perceived Organizational Support, and Organizational Culture on Innovative Work Behavior. This research uses a quantitative approach with the use of questionnaires. The questionnaires were distributed to 276 respondents who are employees of PT Transportasi Jakarta. Data analysis methods will be carried out consisting of descriptive statistical tests, outer model tests consisting of (convergent validity, discriminant validity, composite reliability), and inner model tests. As well as hypothesis testing using full model Structural Equation Model (SEM) analysis with SmartPLS version 3.0. In the full model Structural Equation Model (SEM) not only strengthens the existing theory, but also reveals the relationship between latent variables analyzed through t-tests and significance levels. The results of the study show that servant leadership, perceived organizational support, and organizational culture have a positive influence on innovative work behavior.